Inter Agency Cooperation in Crime Management and Its Implication on Workability of Community Policing Project in Nigeria - M.O., Lawal (2014)
Mamu is one of the communities that are gradually assuming heterogeneity status as a result of steady migration of people for occupation and settlement purpose. Mamu is located in Ijebu North Local Government area of Ogun State. Apart from the influx of settlers, the town has a popular periodic market that always attract people from neighbouring communities as well as people from states like Lagos, Oyo and Ondo States. In spite of high influx of migrants and traders into this community, it is one of the communities that maintain almost zero level of criminal activities. The formal and informal agencies were noted as playing substantial roles in the success being recorded in this situation. Such interactions are the needed requisite for the successful take off of community policing in Nigeria. In view of the constant scenarios of conflicts among the security agencies in Nigeria, the happenings in this community thus become an irresistible issue that needed to be explored for academic purpose. The findings from the community survey carried out in the town revealed that there was strong belief in traditional system hence the resolve of some of them (59%) that they will call on vigilante when in trouble; only 13% agreed to call the police when there is trouble in the community. At the time when some eventually experienced real trouble, only 17% actually called the Police, 55% reported the matter to the Oba-in-council and the vigilante, while 28% did not see the need to report the case. There was strong working relationship between the Police and Vigilante group. Activities of vigilante assisted tremendously in making the act of Policing easier. Those that reported the case to the Police were satisfied with the way the cases were dispensed. The factors responsible for this according to them include thoroughness, adherence to rule of law and the respect for the cooperation the Police is received from the community. This study thus demonstrated the high prospects that with political will, the project of community policing could work in Nigeria Key words: Security, Crime, Crime management, Community Policin